Chromatin-focused genetic and chemical screens identify BRPF1 as a targetable vulnerability in Taxol-resistant triple-negative breast cancer - Ozlem Yedier-Bayram; Ahmet Cingöz; Ebru Yilmaz; Ali Cenk Aksu; Beril Esin; Nareg Degirmenci; Ayse Derya Cavga; Beyza Dedeoğlu; Buse Cevatemre; Hamzah Syed; Martin Philpott; Adam P. Cribbs; et al. (Experimental and Molecular Medicine)
Abstract Triple-negative breast cancer (TNBC) is a particularly aggressive and frequently recurring form of breast cancer, where chemotherapy is the primary treatment approach. Unfortunately, the development of resistance to chemotherapy poses a considerable challenge, restricting the already limited therapeutic alternatives for recurrent cases. Here, we generated two Taxol-resistant TNBC cell lines with a dose-escalation method to mimic chemotherapy resistance in vitro. These cells exhibited reduced growth rates, altered morphology and evasion of apoptosis. Transcriptome analysis uncovered elevated ABCB1 expression and multidrug-resistant phenotype in these resistant cells. To comprehensively investigate the key epigenetic regulators of Taxol resistance, we conducted chromatin-focused genetic and chemical screens and pinpointed Bromodomain and PHD Finger Containing 1 (BRPF1) as a novel regulator of Taxol resistance. Knockout of BRPF1, the reader protein in the MOZ–MORF histone acetyltransferase complex, but not the other complex members, sensitized resistant cells to Taxol. In addition, BRPF1 inhibitors, PFI-4 and OF-1, in combination with Taxol significantly reduced cell viability. Transcriptome analysis upon BRPF1 loss or inhibition revealed a negative impact on ribosome biogenesis-related gene sets, resulting in a global decrease in protein translation in Taxol-resistant cells. CUT&RUN-qPCR analysis demonstrated that BRPF1 directly binds to the ABCB1 promoter, enhancing its expression toward inducing a multidrug-resistant phenotype. Conversely, knockout or inhibition of BRPF1 leads to decreased ABCB1 expression. Our findings uncover a comprehensive molecular framework, highlighting the pivotal role of epigenetic reader protein BRPF1 in Taxol resistance and providing potential avenues for therapeutic intervention in TNBC.